2022
DOI: 10.3389/fnut.2022.890357
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation for Patients With Irritable Bowel Syndrome: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background:Gut microbiota has been identified as an imbalance in patients with irritable bowel syndrome (IBS). Fecal microbiota transplantation (FMT) is a novel method to restore microbiota and treat IBS patients.ObjectiveTo conduct a meta-analysis and estimate the efficacy and safety of FMT for the treatment of IBS patients with subgroup analyses to explore the most effective way of FMT for IBS.MethodsAll eligible studies were searched from PubMed, Embase, Web of Science, and the Cochrane Library through mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…With the growing interest and research in the field of gut microbiome and its link to various diseases, there is also an emergent need to provide practical applications for this gained knowledge and use it to successfully implement targeted modulations with dedicated benefits for human hosts. 19 Although empirical modulation of the microbiome for its therapeutic potential has been performed for over millennia, most popularly via the use of traditional herbal medicine and most recently via faecal microbiota transplantation, [90][91][92] the subject has gained scientific traction in recent years following the continual discovery of bridges linking the gut to various pathophysiological axes. [93][94][95][96][97][98][99][100][101][102][103][104][105] More specifically, with an increasing library of literature investigating the gut microbiome modulation in various metabolic diseases, 39 including diabetes, 28 there is a need for high-quality quantitative syntheses to summarise clinical trials and provide direction for future research in this field by identifying strengths and limitations of available literature.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing interest and research in the field of gut microbiome and its link to various diseases, there is also an emergent need to provide practical applications for this gained knowledge and use it to successfully implement targeted modulations with dedicated benefits for human hosts. 19 Although empirical modulation of the microbiome for its therapeutic potential has been performed for over millennia, most popularly via the use of traditional herbal medicine and most recently via faecal microbiota transplantation, [90][91][92] the subject has gained scientific traction in recent years following the continual discovery of bridges linking the gut to various pathophysiological axes. [93][94][95][96][97][98][99][100][101][102][103][104][105] More specifically, with an increasing library of literature investigating the gut microbiome modulation in various metabolic diseases, 39 including diabetes, 28 there is a need for high-quality quantitative syntheses to summarise clinical trials and provide direction for future research in this field by identifying strengths and limitations of available literature.…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis evaluated the efficacy of FMT in the treatment of IBS and conducted subgroup analyses to determine the factors that influence the efficacy of FMT in IBS. Recently, the meta-analyses of RCTs regarding FMT and IBS were published in the year 2022 ( 23 , 24 ). Consistent with these meta-analyses, we found that FMT does not result in a significant global improvement in IBS patients, but that FMT performed via colonoscopy significantly improved global IBS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The important factors including route of administration, characteristics of stool donors, donor microbiome profile, and patient microbiome profile influence the efficacy of FMT in IBS ( 17 , 18 , 22 ). Recent meta-analyses of RCTs on the efficacy of FMT in IBS have been published ( 23 , 24 ). These meta-analyses demonstrated that FMT does not result in a significant global improvement in IBS patients, but that FMT performed via invasive routes significantly improved global IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the results of the aforementioned studies were combined in a meta-analysis. So, in 4 ( 33 ), 5 RCT ( 34 ) and 7 ( 35 , 36 ) meta-analyses established that FMT doesn’t improve overall IBS symptoms in comparison with placebo. Conversely, a different meta-analysis assessed data from single-arm trials (SATs) and RCTs separately.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous meta-analysis, 2 recent ones published in 2022 similarly do not show significant global improvement in patients with IBS. Nonetheless, FMT operated by invasive routes via colonoscopy or gastroscope significantly improved global IBS symptoms ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%